Anticancer Properties of Natural and Derivative Products - Lupiáñez, José Antonio; Pérez-Jiménez, Amalia; Rufino-Palomares, Eva E. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Natural products are bioactive compounds synthesized by terrestrial and marine plants, microorganisms and animals, whose main objective is to prevent them from attacks by predators and/or pathogens. Traditionally since ancient times, different cultures have used these compounds for the prevention and treatment of various human diseases. During the last few years, it has been reported that most of these phytochemicals possess a variety of interesting and significant biological properties, such as analgesic, antiallodynic, antidiabetic, antioxidant, antiparasitic, antimicrobial, antiviral, antiatherogenic, anti-inflammatory, antiproliferative, antitumor and normal growth stimulants, as well as significant cardioprotective and neuroprotective activity. This thematic book aims to collect and disseminate some of the most significant and recent contributions of the use of the natural compounds called phytochemicals, as well as some of their chemical derivatives, for the prevention and treatment of cancer and other accompanying diseases. On the other hand, in recent years, the synthesis of numerous chemical derivatives of these natural compounds has also intensified, with the aim of enhancing their bioactive capacities. Among all these bioactivities, special attention has been paid to its antitumor capacity through the potential modulation of cancer initiation and growth, cell differentiation, apoptosis and autophagy, angiogenesis, and metastatic dissemination. In addition, a considerable number of studies have linked their anticancer effects to their anti-inflammatory and antioxidant activities.